Perception of Preparers and Users on Sustainability Reporting in Singapore - Chiat, Hwang Soo; ., Wong Dan Chi (Journal of Education and Vocational Research, 2013)
The trend of sustainability reports has increased inexorably as the clamor by various stakeholders including NGOs have been growing louder and louder. In Singapore only a small percentage of listed companies are voluntary providing sustainability reporting but this number is set to increase in line with the world trend. This study attempts to address the perceptions of the importance and usefulness of sustainability reporting, the reporting framework and the training needs of both users and preparers to provide such reports. The results from a survey suggest that the respondents (both undergraduates and managers) perceive sustainability reporting positively and there is a need to provide training especially in the area of integrating financial reporting with sustainability reporting.